Organic-inorganic hybrid graft copolymers of polystyrene and polydimethylsiloxane - Sutherland, Aimee Celeste (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2010.